2022
DOI: 10.25134/fon.v18i1.4453
|View full text |Cite
|
Sign up to set email alerts
|

Eufemisme Dalam Editorial Surat Kabar Tribun Pekanbaru

Abstract: Eufemisme merupakan bentuk ungkapan untuk memperhalus kata-kata yang dirasa kasar atau tidak pantas diucapkan atau didengar oleh orang lain. Eufemisme sangat erat hubungannya dengan bahasa yang ada pada setiap kehidupan manusia dan telah menjadi tata krama atau kesantunan dalam berbahasa. Eufemisme ini juga sering kita jumpai dalam berbagai media massa salah satunya yaitu surat kabar. Rumusan masalah penelitian ini, yaitu Bagaimanakah eufemisme dalam editorial surat kabar harian Tribun Pekanbaru: kajian studi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This study found metaphors such as: (12) cermin keberhasilan means mirror of success, (13) buta aksara means illiteracy, ( 14) melek aksara means literacy, (15) makin diwarnai means influenced by, ( 16) laksana oase di tengah padang pasir means creation of happiness, (17) seperti seberkas sinar di kegelapan means hope in the dark, (18) sorotan publik means public attention, (19) tidak menyentuh means not interfering, and (20) kebangkrutan moral means lack of morality. The use of metaphorical euphemisms is a comparison of two things that are linked by similarities.…”
Section: Periphrasismentioning
confidence: 93%
See 1 more Smart Citation
“…This study found metaphors such as: (12) cermin keberhasilan means mirror of success, (13) buta aksara means illiteracy, ( 14) melek aksara means literacy, (15) makin diwarnai means influenced by, ( 16) laksana oase di tengah padang pasir means creation of happiness, (17) seperti seberkas sinar di kegelapan means hope in the dark, (18) sorotan publik means public attention, (19) tidak menyentuh means not interfering, and (20) kebangkrutan moral means lack of morality. The use of metaphorical euphemisms is a comparison of two things that are linked by similarities.…”
Section: Periphrasismentioning
confidence: 93%
“…Studies about forms of euphemism were performed by [1,2,[8][9][10][11][12][13][14][15][16][17][18][19]. Those research and this study have a similarity in the focus of using euphemism to soften language.…”
Section: Introductionmentioning
confidence: 99%